Patients with cystic echinococcosis in the three national referral centers of Mongolia: A model for CE management assessment. - Bolor Bold; Jan Hattendorf; Agiimaa Shagj; Bayar Tserendovdon; Tsendjav Ayushkhuu; Amgalan Luvsandorj; Jakob Zinsstag; Thomas Junghanss (Public Library of Science (PLoS), 2018)
BACKGROUND:Mongolia is one of the endemic countries for cystic echinococcosis (CE), a zoonotic disease caused by the larval stage of Echinococcus granulosus. The goal of this study is to describe the current clinical management of CE in Mongolia, to capture the distribution of cyst stages of patients treated, and to contrast current practice with WHO-IWGE expert consensus. METHODS:Hospital records of CE patients treated between 2008 and 2015 at the three state hospitals and fulfilling the inclusion criterion 'discharge diagnosis CE' (ICD 10 code B.67.0-67.9) were reviewed. Demographical, geographical, clinical and ultrasonography (US) data were extracted and analyzed. The annual surgical incidence was estimated. The digital copies of US cyst images were independently staged by three international experts following the WHO CE cyst classification to determine the proportions of patients which ideally would have been assigned to the WHO recommended treatment modalities surgery, percutaneous, medical (benzimidazole) treatment and watch & wait. RESULTS:A total of 290 patient records fulfilled the inclusion criteria of the study. 45.7% of patients were below 15 years of age. 73.7% of CE cysts were located in abdominal organs, predominantly liver. US images of 84 patients were staged and assessed for interrater-agreement. The average raw agreement was 77.2%. Unweighted Kappa coefficient and weighted Kappa was 0.57 and 0.59, respectively. Mean proportions of images judged as stages CE1, CE2, CE3a, CE3b, CE4 and CL were 0.59, 0.01, 0.19, 0.08, 0.03 and 0.11, respectively. 40 cysts met the inclusion criteria of treatment modality analysis. The mean proportions of cases with a single cyst assigned to medical, percutaneous treatment, surgery and watch & wait were 52.5% (95% CI 42-65), 25.8% (95% CI 15-30), 5.1% (95% CI 0-10) and 3.3% (95% CI 0-10), respectively. 13.3% (95% CI 5-25) of cysts were staged as CL and therefore assigned to further diagnostic requirement. CONCLUSION:WHO CE cyst classification and WHO-IWGE expert consensus on clinical CE management is not implemented in Mongolia. This results in exclusively surgical treatment, an unnecessary high risk approach for the majority of patients who could receive medical, percutaneous treatment or observation (watch & wait). Introduction of WHO-IWGE expert consensus and training in ultrasound CE cyst staging would be highly beneficial for patients and the health care services.